Improvement of Efficiency in CdS Quantum Dots Sensitized Solar Cells - Wageh, S.; Al-Ghamdi, A. A.; Soylu, M.; Al-Turki, Y.; El Shirbeeny, W.; Yakuphanoğlu, Fahrettin (Polish Acad Sciences Inst Physics, 2013)
CdS quantum dots were coated on TiO2 layer by successive ionic layer adsorption and reaction method. An efficient photovoltaic energy conversion and significant quantum-size effect were observed. The magnitude of the short-circuit photocurrent density J(SC) was found to be approximately 6.01 mA/cm(2) for graphene oxide-incorporated CdS/TiO2 solar cell, while the J(SC) of only CdS-sensitized solar cells was lower than 4.40 mA/cm(2). The efficiency of the CdS/TiO2 solar cell with a graphene oxide layer containing CdS QDs was 60% higher than that of the CdS/TiO2 solar cell. The cell efficiency was remarkably improved with the graphene oxide-incorporation. The carrier recombination of the QDs sensitized solar cells based on CdS-coated TiO2 was significantly suppressed due to photogenerated charge carrier transports resulting from the presence of graphene oxide.
Keywords: Highly Efficient; Graphene Oxide; Collection; Diode; Layer